Penderia Cahaya Bio (Bio-Light Sensor) daripada tumbuhan Mimosa Pudica - Hariyadi Soetedjo; Mohd Noh Dalimin (Universiti Malaysia Sabah, 2000)
Mimosa pudica (M. pudica), a wild tropical plant was investigated their unique bio-sensor phenomena for bio-switching behavior of seismonastic and bio-photosensor of photonastic. Bioswitching behavior was observed for possible movement of their branch (petiole) to raise (ON) and drop (OFF) followed by leaves' movement to close (OFF) and open (ON) when external stimulation (such as touching, heat) triggered to the plant. Bio-photosensor was observed for possible movement of their leaves to open and close due to light intensity changes meanwhile the petiole is in raise position. From the observation carried out to the bio-switching behavior, logical states could be expressed that seems similarly to an electronic switching behavior (ON and OFF). The branch will immediately drop (OFF state) for less than 1 minute after external stimulation triggerred to the plant. Recovery time from drop to raise position was observed from 20 to 30 minutes. For a bio-photosensor detection, by using the ultrasound transceiver (transmitter and receiver), leaves' movement (close and open) as a function of light intensities change was observed. This was carried out by measured ultrasound wave changes (increasing or decreasing) after crossed the leaves as detected by the receiver. The ultrasound flux changes was converted into the electrical current by the receiver. Therefore, leaves' movement will affect to flux changes as can be detected by current changes. This current change is proportional to ultrasound flux changes. An intense bulb lamp (polychromatic) with the adjustable intensity was used as a light source to mimic natural intensity radiation source from the sun. Beside that, for leaves' movement there is a region oflight intensity that able to trigger leaves to start open (from closed) until they open completely, and inversely from open to close completely called as Window of Sensitivity (WoS) that was found to be about 40 to 230 lux.